Consumer Purchasing Intention In The Marketplace Based On The Use Of Vouchers, Pay Later, Flash Sale, And Cash On Delivery (Cod) - Karsono, Lorena Dara Putri; Cahya, Bayu Tri; Choridah, Nur (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
This article explains consumer purchase intention related to vouchers, pay later, flash sales, and cash on delivery (COD). This article uses a type of field research with a quantitative survey approach. The object of this research is youth in Kudus who use the marketplace. The population in this study is not known with certainty, so it uses the Cochran approach to know the sample and get as many as 96 respondents with a purposive sampling technique. Data collection methods used questionnaires, then the data obtained were processed using IBM Statistics. Data analysis techniques used hypothesis testing multiple regression. The results of this study partially show that vouchers, flash sales, and COD positively affect consumer buying interest, and partially paying later does not affect consumer purchase intention.